Medicinal plants used in the community of Campo Preto, Arneiroz, Ceará, Brazil - Brito, Selma Freire de; Evangelista, Antônio Wanderson Lopes (Revista Verde de Agroecologia e Desenvolvimento Sustentável, 2020)
Ethnobotany has the role of helping to understand the relationships between men and plants in a community. The objective of this research was to carry out a survey on medicinal plants used in the community of Campo Preto, Armeiroz, Ceará, located in a region of Caatinga. The data were obtained through a previously prepared interview that sought to identify the people who use it; which medicinal plants are used; the forms of preparation; the parts used; where these plants are obtained; and what diseases these medicinal plants are used for. Most of the interviewees have incomplete elementary education and learned about medicinal plants from someone in the family. Nineteen plants were cited, the most cited being Lippia alba. The community resorts to the use of plants mainly to fight colds being prepared in the form of tea. It draws attention to the high number of exotic species used by the community. Finally, it is known that medicinal plants are used by all interviewed families, emphasizing the need to know and encourage the use of species of native flora.